Metal-free carbon nitride as a fluorescence sensor for nitrate ions - Alim, Nor Shuhada (2015)
In this study, a metal-free carbon nitride (CN) was investigated for the first time as a potential fluorescence sensor for detection of nitrate ions (NO3 -). The CN was prepared through thermal polymerization of urea precursor at 823 K and characterized by diffuse reflectance ultraviolet-visible (DR UV-vis), Fourier transform infrared (FTIR), and fluorescence spectroscopies. The DR UVVis spectrumconfirmedthat CN could absorb light up to 430 nm. On the other hand, the FTIR spectrum revealed the presence of graphitic CN single and double bond characters in the 800- 1700 cm-1 region. From the fluorescence spectroscopy, two excitation peaks at 278 and 369 nm were observed due to the presence of N=C and N-C groups, respectively. The fluorescence sensor capability of the CN was then investigated usingdifferent concentrations of NO3 - (300-1800 µM).It was confirmed that the intensity of the emission site excited at either 278 or 369 nm was quenched linearly with the concentrations of the NO3 -. The Stern-Volmer plots showed that the quenching rate for N=C and N-C was 210-4 and 110-4µM-1, respectively. These results suggested that CN might act as a fluorescence sensor for NO3 -.